Hubungan vo2max dengan kecepatan pemulihan asam laktat setelah latihan fisik submaksimal - Dita Yuliastrid, (Ilmu Keolahragaan, 2013)
Abstract :VO2 reflects ones fitness level as a capital for a good athlete besides motivation and basic movement. A high VO2 max can inhibits fatigue caused by accumulated lactic acid in blood. The purpose of this research is to find out the correlation between VO2 max and the velocity of lactate acid recovery after sub maximum physical exercise. The samples were 20 people, divided into two groups, each groups consisted of 10 persons. The first group (untrained) had VO2 max 35-40 ml/kg/min and the second (trained) had 55-60 ml/kg/min. Both groups did sub maximum physical exercise (85% HRM) using ergocycle. The blood lactic acid level was taken as the data from the fingertips three times; before the exercise, after 5 minutes and 15 minutes recovery. The average of group 1s initial lactic acid was 1.86 ± 0.1955 mMol/l and group 2 was 1.55 ± 0.2014 mMol/l; the average lactic acid after 5 minutes recovery of group 1 was 6.61 ± 0.4408 mMol/l and group 2 was 5.62 ± 0.3994  mMol/l; after 15 minutes recovery, group 1 was 5.96 ± 0.568 mMol/l and group 2 was 2.85± 0.7821 mMol/l. The average decrease of group 1s lactic acid was 0.650 ± 0.369 mMol/l and group 2 was 2.770 ± 0.693   mMol/l. The pace of group 1s lactate decrease was  6.5x10-2 ± 3.69 x 10-2 mMol/l minutes and group 2 was 0.277 ± 6.93 x 10-2 mMol/lminutes. The result of ANAVA univariate test showed that the difference of the lactic acid decrease and the recovery pace between group 1 and 2 was very significant (p<0.05) and R Square value was 0,836. There was corelation between VO2 max and the velocity of lactic acid recovery after sub maximum physical exercises ;and the recovery of blood lactic acid level after sub maximum physical exercise was faster in a group with 55-60 ml/kg/min of  VO2 max than in a group with 35-40 ml/kg/min of  VO2 max.   Key words : VO2 max, lactic acid, sub maximum physical exercises.